2019
DOI: 10.1111/aeq.12324
|View full text |Cite
|
Sign up to set email alerts
|

Preaching to the Choir: University Diversity Committees as Affective Communities

Abstract: This paper asks, what significance do diversity committee meetings have for how diversity workers experience, make sense of, and navigate the challenges of diversity work at a large, public research university? Drawing on a sixteen-month ethnography of diversity policy and practice, I analyze the practice of "preaching to the choir" among committee members and explore the different affective attachments that form between diversity workers, their works, and the objects of diversity interventions. [affect theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…We have no nothing". Previous research on the work of diversity-related initiatives like committees have demonstrated the central role of goal-setting in mobilizing productive change (Anderson 2020;Leon and Williams 2016). Clearly, any top-down religious diversity initiative should provide clear direction with any initiative designed to reflect a sustained institutional posture toward productive religious engagement.…”
Section: Discussionmentioning
confidence: 99%
“…We have no nothing". Previous research on the work of diversity-related initiatives like committees have demonstrated the central role of goal-setting in mobilizing productive change (Anderson 2020;Leon and Williams 2016). Clearly, any top-down religious diversity initiative should provide clear direction with any initiative designed to reflect a sustained institutional posture toward productive religious engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Advancing diversity, equity, and inclusion must go beyond mere diversity statements; to be successful, its elements must permeate the institution's strategic plans, and the fruits of its labor must be evident and measurable (Figure 2). American idiom "preaching to the choir" as a metaphor to highlight shared similarities in race, gender, and partnerships made through diversity committee work (Anderson, 2020). Anderson described the different challenges related to committee work as a burden, whereby Chief Diversity Officers often reported feeling dissatisfied and even marginalized due to a lack of adequate support and institutional resources.…”
Section: The Challenges Faced By Diversity Committeesmentioning
confidence: 99%